PENGARUH DANA ALOKASI UMUM (DAU) DAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP BELANJA MODAL DAN KEMANDIRIAN KEUANGAN DAERAH PROVINSI SULAWESI TENGGARA - Lestari, Anita; Dali, Nasrullah; Abdullah, Muntu (JPEP (Jurnal Progres Ekonomi Pembangunan), 2016)
The aim of this study was to determine: 1) the effect of DAU on capital expenses; 2)the effect of PAD on capital axpenses; 3) the effect of DAU on the independence of localfinance, 4) the effect of PAD on the independence of local finance. 5) the effect of CapitalExpenses on the independence of local finance.Data were collected by conducting a surveyand were examined with the multiple linear regression analysis using the SPSS program.Results of the study showed that the value ratio of the local financial independence ofSoutheast Sulawesi in the period from 2003 to 2015 was still categorized as low. Result ofpartial regression analysis indicated that for the first equation only DAU had positive andsignificant effect on capital expenses, whereas for the second equation both PAD and capitalexpenses variables had positive and significant effect on the local financial independence.Simultaneously, the first equation showed that DAU and PAD had positive and significanteffect on capital expenses, and so was the second equation, which showed that DAU, PAD,and capital expenses had positive and significant effect on the local financial independence.The study recommended that the local goverment continues its effort to reduce its bigreliance on DAU (general allocation budget).Keywords: General Allocation Budget, Local Revenue, Capital Expenses, Local FinancialIndependence.